2017
DOI: 10.1002/hed.24858
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution cone-beam computed tomography for assessment of bone invasion in oral cancer: Comparison with conventional computed tomography

Abstract: A CBCT offers marginally improved sensitivity at the cost of reduced specificity for assessment of bone invasion compared to CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…In terms of using CBCT or CT for diagnostic accuracy, we did not find any difference. This matter has been confirmed by other authors [6].…”
Section: Discussionsupporting
confidence: 87%
“…In terms of using CBCT or CT for diagnostic accuracy, we did not find any difference. This matter has been confirmed by other authors [6].…”
Section: Discussionsupporting
confidence: 87%
“…In 2017, Czerwonka and colleagues compared CBCT with conventional CT and reported that the sensitivity and specificity values for CBCT were 91% and 60%, respectively, whereas those for CT with bone windows were 86% and 68%, respectively. 8 These reports provide a basis for the use of CBCT in evaluations of tumor bone invasion. In our study, CBCT predicted bone invasion with 100% accuracy, a higher level than those reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, compared to histological results, the bone invasion presented on panoramic radiograph was smaller with 13mm in width and 2 mm in depth; and was smaller with 5 mm in width and larger with 3 mm in depth on spiral CT. A systematic review compared several modalities in detecting mandibular invasion by OSCC, the results showed that the sensitivity of bone invasion diagnosis for magnetic resonance imaging, CBCT, spiral CT and panoramic radiography was 94%, 91%, 83%, and 55% and the speci city was 100%, 100%, 97% and 91.7% for magnetic resonance imaging, CBCT, positron emission tomography/CT and panoramic radiography respectively [7]. Czerwonka et al compared the diagnosis e ciency of CBCT with conventional spiral CT, they found that the sensitivity and speci city were 91% and 60% for CBCT and were 86% and 68% for spiral CT [8].…”
Section: Discussionmentioning
confidence: 99%